Dictionary of economic terms - Andres, Tomas Quintin Donato; Vergel, Virgilio P. (Quezon City Giraffe Books, 1995)
This is a dictionary that contains economic terms, its definitions and explanations of the meanings of the specialized terms. It provides easy access to a wide range of economic terms as a comprehensive guide for those beginning a career in economics, teachers, professors and economists, consultants, students of economics and allied subjects, and businessmen in general.
"This Dictionary of economic terms provides a concise but comprehensive guide to the world of economics. It gives clear definitions of the specialized terms used in economics in a manner comprehensive to the ordinary reader." Arranged in alphabetical order.
Keywords: Economics -- English. -- Dictionaries